UUM listed in top 200th placing - New, Sunday Times (New Sunday Tribune, 2017)
ALOR SETAR: Universiti Utara Malaysia (UUM) has been listed in the top 200+ placing in the first edition of the Times Higher Education Asia-Pacific University Rankings (THE APAC) 2017 which was announced recently.